Kajian Nilai Keawetan Reclaimed Asphalt Pavement Dengan Pemanfaatan Buton Granular Asphalt Pada Lapis Perkerasan Ac-Wc - Muhammad Yasir; Fadrizal Lubis; Widya Apriani* (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
Reclaimed Asphalt Pavement (RAP) is the residual waste generated from the dredging of damaged road pavements. Usually this RAP material is thrown away so it is rarely reused. In fact, RAP material that has become waste and is no longer used can be used as an added ingredient in the manufacture of new asphalt concrete with rejuvenator. This study aims to determine the durability value of reclaimed asphalt pavement with the use of buton granular asphalt (BGA) as a rejuvenating agent in the gradation of the Laston mixture (AC-WC) against the IRS value. The first testing stage is to test the characteristics of the reclaimed asphalt pavement material and then continue with the marshall test. The optimum asphalt content value obtained after testing is at 5,28% of the total aggregate. The reference used in testing the characteristics of Marshall and IRS is the specification of Bina Marga in 2018 revision 2. The results of the IRS test using the optimum asphalt content of 5,28% with the addition of BGA show that along with the increase in the level of BGA in the AC-WC mixture by using RAP, the ability of the mixture to withstand the load increases and the flexibility of the mixture decreases, so that the asphalt's durability increases, represented by the IRS test of 30 minutes and 24 hours which shows the durability value with 0% BGA content, the value is 112,70%, with the addition of BGA 1% obtained a value of 118,87%, BGA 2% 121,50% and with the addition of 3% BGA content which was 125,11% in the Laston mixture (AC-WC). So from the test results, the IRS value meets the requirements of the 2018 Highways Specification of 90%, so it is concluded that the results of the tests carried out meet the durability requirements and can be applied in the field.